Sexual narcissism and its association with sexual and well-being outcomes. (1st January 2020) - Klein, Verena; Reininger, Klaus Michael; Briken, Peer; Turner, Daniel
Abstract: Theories on narcissism are traditionally closely related to sexuality. Most research on the association between narcissism and sexual behavior, however, has focused on harmful/maladaptive outcomes. The aim of the present two studies was to examine the possible health-promoting influence of both global and sexual narcissism on sexual function and genital self-image. In Study 1, sexual narcissism was positively associated with sexual functioning in both women and men ( N = 505, online-recruited German participants). In the women's sample, sexual narcissism was related to a positive genital self-image. The facet sexual skill was identified as the most important predictor for sexual function and positive genital self-image in both women and men. Study 2 replicated and extended this association in an online sample of US Americans ( N = 588) by including quality of life measures. Underscoring the benign nature of the sexual skill facet, this subscale was associated with quality of life in both women and men. The idea of a possible beneficial influence of sexual narcissism on sexuality related outcomes is discussed.